Budd-Chiari syndrome treated by Senning operation. Issue 6 (June 1988) - Mahony, M J; Littlewood, J M; Losowsky, M S; Robinson, P J; Giles, G R
Abstract : Budd-Chiari syndrome was diagnosed in a 13 year old boy who presented with ascites. Angiographic studies showed occlusion at the ostia of the hepatic veins. This was treated surgically by the Senning operation of transcaval dorsocranial resection of the liver and hepatocaval anastomosis. The patient's ascites cleared and he remains well 10 months after surgery.